PENERAPAN SISTEM TERDISTRIBUSI PADA TOGETHER IN A SINGLE CONNECTION (TSC) BERBASIS WEB - Zuliana Zuliana; Hero Wintolo; Bambang Sudibya (Compiler, 2013)
Distributed system is a computer networking technology which can be hardware or software. In hardware distributed system by a collection of computers that are heterogeneous, being in the software system is distributed in the form of software that connects two applications in the form of client and server side. TSC method is a method that already existed before, which can be used increase the ranking o f a blog. Implementation distributed system for TSC using landing page as the intermediary. Landing page serves as a liaison between web applications or blogs are listed as a member to raise the ranking of a database on the application server side. When someone does click on landing page seoindonesia, will open a blog or other web members. Landing page so it can be used as a way to count the number of visitors to a blog or website, which in turn can increase the number o f page visits and 1 with 1 clickbutton seoindonesia for test in histats.com.